Farmers' Participation as an Accelerator in Digital Agriculture in Kendal Regency - Wulan Sumekar; Siwi Gayatri; Alexander Morados (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The study was conducted to describe the level of farmers' participation and analyze the factors influencing their participation in adopting digital communication and information technology in farming activities. The research was carried out from July to December 2023 in Tampingwinarno Village, one of the villages in Sukorejo Subdistrict, Kendal Regency. This location was selected because the village's primary economic activities have shifted from rice farming to guava plantations accompanied by downstream industries. The respondents were active members of farmer groups engaged in agriculture especially cassava and guava products and utilizing internet access through social media for product marketing and communication among farmers. The total number of respondents was 125. Primary data were collected through interviews using a questionnaire as a reference, along with field observations. The data were analyzed using multiple linear regression. The results showed that the average level of farmers' participation was relatively high (64.01%). Experience, equality, access, business complexity, age, and education significantly influenced participation simultaneously (p < 0.001) with an R² of 0.7549. Partially, factors like access (p < 0.001), business complexity (p < 0.05), equality (p < 0.1), and education (p < 0.1) affected farmers' participation in adopting digital communication and information technology. Farmers' participation can accelerate digitalization in the 5.0 era to enhance farmers' competitiveness.